Anions of α-Amino Acids as (O,N)-Donor Ligands in Si-, Ge- and Sn-Coordination Chemistry - Anne Seidel; Jörg Wagler (Molecules)
This review gives an overview of Si-, Ge- and Sn-compounds with (O,N)-bi- and -oligodentate ligands, which have the α-amino carboxylic acid motif N–C(R,R′)–C(=O)O in common (R,R′ = H or hydrocarbyl). While the amino acids themselves are encountered as mono- and di-anionic ligands, modifications at the N-terminus (e.g., extension of the ligand backbone by, e.g., additional alkane carboxylic acid groups) give rise to a wealth of ligands, which bear the α-amino carboxylic acid motif. With particular interest in the coordination features of these ligands, crystallographically characterized complexes are the focus of this review.